Principles of Polymer Engineering (2nd Edition) - McCrum, Norman Gerard; Buckley, C. P.; Bucknall, C. B. (Oxford University Press, 1997)
This book brings up-to-date coverage for undergraduates studying materials and polymer science. The opening chapters show why plastics and rubbers have such distinctive properties and how they are affected by temperature, strain rate, and other factors. The rest of the book concentrates on how these properties can be exploited to produce functional components within the constraints placed on them. The main changes for the second edition are a new chapter on environmental issues and substantially rewritten sections on yield and fracture and forming.